(untitled) (The Agriculturists, 2014)
A field experiment was conducted at the Horticulture Farm of Sher-e-Bangla Agricultural University, Dhaka with a view to study character association and path analysis in six strawberry genotypes. The trial was laid out in a Randomized Complete Block Design with three replications. Data on crown height, number of flower buds per plant, number of flowers per plant, number of fruits per plant, length and breadth of fruit and fruit yield per plant were collected. All the characters showed significant correlation with fruit yield. Path analysis revealed that crown height, number of flowers per plant and length of fruit had the positive direct effect on yield per plant. Number of flower buds per plant, number of fruits per plant and breadth of fruit had negative direct effect on yield per plant. DOI: http://dx.doi.org/10.3329/agric.v11i2.17491 The Agriculturists 2013; 11(2) 74-78